THE EFFECT OF LEAD ACETATE ON THE NEURO-IMMUNO-ENDOCRINE REGULATION OF THE ORGANISM AND THE NUMBER OF HEMATOLOGICAL MARKERS - Ismayilov, Yu.B.; Salimli, T.A.; Ismayilova, A.T.; Iskandarova, Z.Sh.; Jafarova, G.K. (World of Medicine and Biology, 2023)
Changes in the cell composition of the blood of rats that occurred under the effect of toxic stress caused by lead acetate have been studied. The blood cells of the control group animals corresponded to the physiological norm because they were kept under optimal conditions. However, the number of blood cells in the rats exposed to the toxic effect caused by lead acetate changed sharply. The toxic stress condition changes the number of specific and non-specific cells that provide the immune response of the organism in different directions. Depending on the duration of the toxic stress caused by lead acetate, there are various directional changes in the number, percentage composition, and distribution density of hematological indicators in the blood, and the mechanisms that ensure the homeostasis and hemostasis of the body are disturbed. Therefore, it is important to conduct research aimed at developing ways to correct toxic stress caused by intensive environmental pollution.
Keywords: extreme condition; stress; heavy metal; monoamine; hormone; immunoreactivity